1993
DOI: 10.1007/bf00911313
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety disorders in African-American and white children

Abstract: There are little available data on African-American children with anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
59
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 15 publications
8
59
1
1
Order By: Relevance
“…Further, a study conducted by Nalven (1970) examining differences in anxiety disorders among African American and Caucasian children found that African Americans from low socioeconomic areas reported more animal fears than their Caucasian counterparts. Although these differences were observed between African American and Caucasian children, Last and Perrin (1993) observed that African American and Caucasian children were more similar than different in anxiety symptomatology and that they were also found to be more similar than different on a measure of anxiety sensitivity (Ginsburg & Drake, 2002). Given that African American manifestations of anxiety seem to be heavily influenced by culture, parental contributions to child anxiety manifestation need to be considered.…”
Section: Anxiety Disorders In African American Childrenmentioning
confidence: 78%
See 4 more Smart Citations
“…Further, a study conducted by Nalven (1970) examining differences in anxiety disorders among African American and Caucasian children found that African Americans from low socioeconomic areas reported more animal fears than their Caucasian counterparts. Although these differences were observed between African American and Caucasian children, Last and Perrin (1993) observed that African American and Caucasian children were more similar than different in anxiety symptomatology and that they were also found to be more similar than different on a measure of anxiety sensitivity (Ginsburg & Drake, 2002). Given that African American manifestations of anxiety seem to be heavily influenced by culture, parental contributions to child anxiety manifestation need to be considered.…”
Section: Anxiety Disorders In African American Childrenmentioning
confidence: 78%
“…In general, children of anxious parents are seven times more likely than children of nonanxious parents to develop an anxiety disorder (Turner, Beidel, & Costello, 1987), however there is a dearth in the literature in regards to anxiety disorders in African American children (Last & Perrin, 1993;Neal & Brown, 1994;Neal & Turner, 1991). Overall, studies addressing anxiety in African American children have yielded mixed results.…”
Section: Anxiety Disorders In African American Childrenmentioning
confidence: 98%
See 3 more Smart Citations